The Role of Calcium–Calcineurin–NFAT Signaling Pathway in Health and Autoimmune Diseases - Park, Yune-Jung; Yoo, Seung-Ah; Kim, Mingyo; Kim, Wan-Uk (Frontiers in Immunology, 2020)
Calcium (Ca2+) is an essential signaling molecule that controls a wide range of biological functions. In the immune system, calcium signals play a central role in a variety of cellular functions such as proliferation, differentiation, apoptosis, and numerous gene transcriptions. During an immune response, the engagement of T-cell and B-cell antigen receptors induces a decrease in the intracellular Ca2+ store and then activates store-operated Ca2+ entry (SOCE) to raise the intracellular Ca2+ concentration, which is mediated by the Ca2+ release-activated Ca2+ (CRAC) channels. Recently, identification of the two critical regulators of the CRAC channel, stromal interaction molecule (STIM) and Orai1, has broadened our understanding of the regulatory mechanisms of Ca2+ signaling in lymphocytes. Repetitive or prolonged increase in intracellular Ca2+ is required for the calcineurin-mediated dephosphorylation of the nuclear factor of an activated T cell (NFAT). Recent data indicate that Ca2+-calcineurin-NFAT1 to 4 pathways are dysregulated in autoimmune diseases. Therefore, calcineurin inhibitors, cyclosporine and tacrolimus, have been used for the treatment of such autoimmune diseases as systemic lupus erythematosus and rheumatoid arthritis. Here, we review the role of the Ca2+-calcineurin–NFAT signaling pathway in health and diseases, focusing on the STIM and Orai1, and discuss the deregulated calcium-mediated calcineurin-NFAT pathway in autoimmune diseases.